Electrochemical synthesis of tetrazoles via metal- and oxidant-free [3 + 2] cycloaddition of azides with hydrazones. Issue 23 (13th November 2018) - Ye, Zenghui; Wang, Feng; Li, Yong; Zhang, Fengzhi
Abstract : An unprecedented electrochemical [3 + 2] cycloaddition reaction for the synthesis of valuable tetrazoles was developed. Readily available azides and hydrazones were used as the starting materials under simple metal- and oxidant-free reaction conditions. Various functional groups are compatible with this green protocol. Abstract : An unprecedented electrochemical [3 + 2] cycloaddition reaction for the synthesis of valuable tetrazoles was developed. Readily available azides and hydrazones were used as the starting materials under simple metal- and oxidant-free reaction conditions. Various functional groups are compatible with this green protocol which can be carried out on a gram-scale or in one pot easily.